The influence of Radiotherapy on some of coagulation parameters in patients with Non Small Cell Lung Cancer (NSCLC) - Ziółkowska, Ewa; Roszkowski, Krzysztof; Sitarz, Radosław (Contemporary Oncology/Współczesna Onkologia, 2005)
The aim of this study was to estimate the influence of radiotherapy on the concentration of selected factors of the fibrinolysis system in patients with non-small cell lung cancer disease (NSCLC). The studied group included 30 patients (27 men and 3 women) aged from 41 to 71 years with various stages of clinical progression of NSCLC. Some of the patients underwent an operation and for all the radical radiotherapy in a dose of 50-60 Gy/5 a week/2 Gy/fraction was applied. In all patients the following parameters were marked: concentration of fibrinogen, concentration of t-PA, concentration of PAI-1 and concentration of plasmin-a-2-antiplasmin complex (PAP), before radiotherapy, after a dose of 50 Gy/g and after a dose of 60 Gy/g. 10 healthy persons made up the control group. This study showed a statistically significant increase of all the parameters mentioned above in the group of patients with NSCLC compared to the control group. The mean concentration of fibrinogen increased during radiotherapy both after the doses of 50 as well as 60 Gy/g. The concentrations of t-PA and PAI-1 went up after the dose of 50 Gy/g (p<0.001), however, after the dose of 60Gy/g fell to the similar values as those noted in the control group. It was affirmed that the concentration of PAP in the patients with NSCLC was at a higher level than that in the control group. However, the mean concentrations of PAP after radiotherapy fell to the similar values as in the healthy group. The clinical disorders were not observed in all patients, only irregularity at the molecular level was affirmed. Conclusions: 1) Radiotherapy causes the growth of fibrinogen\'s activity in patients with NSCLC, but it not evoking the clinical disorders in the treated patients. 2) Measurement of the concentration some parameters of hemostasis creates the possibility of their use as prognostic markers in irradiated patients with lung cancer.